2005
DOI: 10.4049/jimmunol.174.11.7403
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fibrinogen-Like Protein 2 Prothrombinase/Fibroleukin in Experimental and Human Allograft Rejection

Abstract: Immune coagulation is a major contributor to the pathogenesis of xenograft rejection, viral-induced hepatocellular injury and cytokine-induced fetal loss syndrome. In this study, we investigated the contribution of the novel gene product, fibrinogen-like protein 2 (fgl2) prothrombinase, in mediating immune injury in experimental and human acute allograft rejection. Using a mouse heterotopic cardiac transplant model, mouse fgl2(mfgl2)/fibroleukin mRNA transcripts and protein were highly expressed in macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 25 publications
3
55
0
Order By: Relevance
“…Furthermore, cardiac grafts from fgl2 Ϫ/Ϫ mice were resistance to thrombosis, suggesting a role for endothelial cell fgl2 expression in the fibrin deposition associated with allo-and xenotransplantation rejection. In contrast, Ning et al (13) and Hancock et al (16) showed that fgl2 Ϫ/Ϫ mice rejected fully mismatched allografts, supporting the contention that the endothelium, but not leukocytes, maybe more important for fibrin deposition in allotransplant rejection.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Furthermore, cardiac grafts from fgl2 Ϫ/Ϫ mice were resistance to thrombosis, suggesting a role for endothelial cell fgl2 expression in the fibrin deposition associated with allo-and xenotransplantation rejection. In contrast, Ning et al (13) and Hancock et al (16) showed that fgl2 Ϫ/Ϫ mice rejected fully mismatched allografts, supporting the contention that the endothelium, but not leukocytes, maybe more important for fibrin deposition in allotransplant rejection.…”
mentioning
confidence: 73%
“…These proteins have been shown to exhibit coagulant and angiogenic activity, as well as immunoregulatory activity (1,2,30). Similar to other members of the fibrinogen superfamily, our laboratory has recently discovered (19) that FGL2 inhibits murine DC maturation and adaptive T cell immune responses, in addition to its role in innate immunity through its ability to activate the coagulation system (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plates were coated and incubated overnight with 2 g/mL monoclonal anti-FGL2 (6H12) (IgG1) as a capture antibody. Plasma samples (50 L) were added to each well, and after a 1-hour incubation at 37°C and three washes with Tris-Tween buffered saline, the wells were incubated with 2 g/mL polyclonal rabbit anti-FGL2 antibody 15 for 2 hours at 37°C. The plate was washed again, and polyclonal anti-FGL2 binding was detected with a secondary horseradish peroxidase-conjugated anti-rabbit antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Predicted as a type II transmembrane glycoprotein [2], cell membraneassociated FGL2 was shown to exhibit novel prothrombinase activity when associated with cell membranes/phospholipid vesicles [3,4], which has been implicated in the pathogenesis of experimental and human viral-induced fulminant hepatitis [2], cytokine-induced fetal loss syndrome [5], allograft [6] and xenograft rejection [7]. The procoagulant activity was shown to depend on the serine 89 at the linear N terminal domain of FGL2 [4].…”
Section: Introductionmentioning
confidence: 99%